A bicriteria mixed-integer programming model for delay management in train timetabling. Issue 3 (19th May 2017) - Rana, Sambit Sekhar; Nayak, Rupaj Kumar
Abstract: Delay management in train is a necessary issue in these days. If a train arrives at some station with a delay, it is to be determined if the connecting train ought to stay up for transmuting passengers or it should depart in time. The goal is to minimize the passengers' inconvenience i.e. delay, he has when reaching his final destination. The delay can be approximated by a combining number of missed connections and by the adding all the arrival delays of all the trains. The present paper deals with the delay management problem in train timetabling. We focuses only on modeling part of delay management in train timetabling which is modeled as a bicriteria mixed integer linear program.